Prevention of Anterior Cruciate Ligament Injuries in Competitive Adolescent Alpine Skiers - Maria Westin; Marita Löfgren Harringe; Björn Engström; Marie Alricsson; Suzanne Werner (Frontiers Media S.A., 2020)
Anterior cruciate ligament (ACL) injury is one of the most serious injuries among Swedish alpine ski high school students. An ACL injury forces the skier to stop skiing for several months, and some skiers even have to give up their skiing career. Therefore, an ACL injury prevention program might play an important role for alpine skiers. In the present study ski high school students have been followed in terms of ACL injuries during 1-2 ski seasons between 2006/2007 and 2012/2013. Alpine skiers studying at the Swedish ski high schools during the ski seasons 2011/2012 and 2012/2013 received a specific ACL injury prevention program (n = 305), while alpine skiers who attended a Swedish ski high school between the ski seasons 2006/2007 and 2010/2011 served as controls (n = 431). The prevention program was based on earlier studies and included indoor and outdoor exercises on snow focusing on core stability and neuromuscular control. Alpine skiing is an equilateral sport. Therefore, the goal of the prevention was to encourage the skiers to practice these exercises in order to perform equally good on both legs. The outcome measure consisted of the number and incidence of ACL injuries. The 2 years of prevention resulted in 12 ACL injuries (3.9%) compared with 35 ACL injuries during the control period (8.1%). The absolute risk rate showed a decreased incidence rate of −0.216 [CI −0.001-(−0.432)]/100 months attending a ski high school in favor of the intervention group. A prevention program focusing on the skier's ability to perform neuromuscular exercises equally good on both legs led to a reduction of ACL injuries.